Selective Liquid‐Phase Sorption of Small Aliphatic Normal Alcohols on a Flexible Assembly Composed of Keggin Polyoxometalate. Issue 5 (8th February 2017) - Harati, Seyed Mohsen; Mahjoub, Ali Reza; Hemmati, Mahmood
Abstract : Single crystals of Na3 [Fe3 O(O2 CCH2 OCH3 )6 (H2 O)3 ][α‐SiW12 O40 ]· 13.5H2 O (1a ) and their nanoparticles (2a ) have been synthesized by self‐assembly of the constituent ions and a one‐pot sonochemical reaction, respectively. Their corresponding activated phases, 1b and2b, were obtained by desorption of crystallization water through a thermal process. The sorption capacity of2b for methanol vapor, owing to the lack of well‐defined pores, was significantly less than1b, which was confirmed by thermogravimetric analysis. Liquid‐phase sorption of small aliphatic alcohols (C1 –C4 ) was applied to characterize the sorption behavior of1b . The lattice flexibility was revealed by unit‐cell volume calculation for1b after sorption of each alcohol by using powder X‐ray diffraction data. Also, investigation of the sorption isotherms, fitting experimental kinetic data to the Lagergren and Ho models, and calculation of the activation energies for sorption of each alcohol were carried out. Finally, the sorption selectivity of1b towards the alcohols was determined. Abstract : Sorption isotherms and kinetics of normal aliphatic alcohols on a new polyoxometalate‐based ionic crystal were evaluated in the liquid phase. The single‐crystal structure was studied by X‐ray crystallography, its flexibility was confirmed by unit‐cell volume calculations after sorption of various guests, and the selectivity was assessed in a mixture of C1 –C4 normal alcohols.